2018
DOI: 10.1038/s41598-018-30660-x
|View full text |Cite
|
Sign up to set email alerts
|

The establishment of a marine focused biorefinery for bioethanol production using seawater and a novel marine yeast strain

Abstract: Current technologies for bioethanol production rely on the use of freshwater for preparing the fermentation media and use yeasts of a terrestrial origin. Life cycle assessment has suggested that between 1,388 to 9,812 litres of freshwater are consumed for every litre of bioethanol produced. Hence, bioethanol is considered a product with a high-water footprint. This paper investigated the use of seawater-based media and a novel marine yeast strain ‘Saccharomyces cerevisiae AZ65’ to reduce the water footprint of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 35 publications
1
54
0
1
Order By: Relevance
“…Yeasts, especially S. cerevisiae, are used for bioethanol production, but wild S. cerevisiae has been described as moderately osmotic and salt tolerant compared with other yeasts. 22,23 Marine yeasts have been reported as promising candidates for the production of bioethanol and other chemicals, as they possess high salt tolerance. 22 Previous studies have revealed that there is a wide range of phenotypic responses in the presence of these inhibitory compounds in yeasts and yeasts with a tolerant phenotype perform better in fermentation in the presence of these inhibitory compounds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yeasts, especially S. cerevisiae, are used for bioethanol production, but wild S. cerevisiae has been described as moderately osmotic and salt tolerant compared with other yeasts. 22,23 Marine yeasts have been reported as promising candidates for the production of bioethanol and other chemicals, as they possess high salt tolerance. 22 Previous studies have revealed that there is a wide range of phenotypic responses in the presence of these inhibitory compounds in yeasts and yeasts with a tolerant phenotype perform better in fermentation in the presence of these inhibitory compounds.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Marine yeasts have been reported as promising candidates for the production of bioethanol and other chemicals, as they possess high salt tolerance. 22 Previous studies have revealed that there is a wide range of phenotypic responses in the presence of these inhibitory compounds in yeasts and yeasts with a tolerant phenotype perform better in fermentation in the presence of these inhibitory compounds. 24 Research has revealed that marine yeast strains have the ability of converting monomeric hexose sugars into ethanol more efficiently than terrestrial yeast strains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microalgae are particularly interesting as they may be farmed in saline water and wastewater streams . Other important developments are related to the production of bioethanol by marine yeast species, even though bioethanol is considered a product with a high‐water footprint …”
Section: Applications Of Mnps In Biotechnology Bioengineering and Pmentioning
confidence: 99%
“…Various filamentous fungi, such as certain Trichoderma and Aspergillus species, have been reported to produce bioethanol as the main fermentation product from lignocellulosic biomass, directly. These fungi are thought to contain two biological systems: one system produces cellulase enzyme for degradation of cellulose to fermentable sugars under aerobic conditions; the second system produces ethanol under anaerobic conditions (Greetham, Zaky, & Du, ; Greetham, Zaky, Makanjuola, & Du, ; Zaky, Greetham, Tucker, & Du, ). However, although Trichoderma and Aspergillus are able to utilize five of the lignocellulosic sugars (glucose, mannose, galactose, xylose, and arabinose) and the ability of direct fermentation of lignocellulose to bioethanol, they do not produce bioethanol with high yield and high rate.…”
Section: Introductionmentioning
confidence: 99%